PENGGUNAAN COOPERATIVE LANGUAGE LEARNING METHOD PENGAJARAN BAHASA INGGRIS PADA GURU TUTOR DI LEMBAGA BIMBINGAN BELAJAR - Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
Abstract: Community service held at Bimbingan Belajar Rumah Pintar Q-ta in Jl. Setu Pedongkelan Cimanggis Kelapa Dua Depok purposes to share knowledge and information related to the use of Cooperative Language Learning (CLL) Method in teaching English particularly for primary and secondary schools level. Besides, this activity gives either theoretical concepts or practical implementation of CLL Method for the instructors by self-applying of some techniques of CLL. This service contains training and workshop for instructors conducted during June-Juli 2016. Key words: Cooperative Language Learning, English Teaching